Analisis Pemasaran Sayuran Hidroponik ( Studi Kasus : Syifa Hidroponik Medan ) - Hakim, Mukti; Fuad, Fuad; Gea, Fandersius (JURNAL AGROPLASMA, 2024)
Hydroponic technology has many advantages compared to traditional planting techniques. The advantages of hydroponics include being environmentally friendly, hygienic products, faster plant growth, maintained crop quality, and increased quantity. The target market segment is generally the upper middle class. Hydroponic vegetables contain lots of vitamins and nutrients for health, hydroponic vegetables that are marketed are of very high quality so that they have high economic value. The purpose of the study is to determine the marketing channels and marketing institutions for hydroponic vegetables at Syifa Hydroponic Medan. This study was conducted at Syifa Hydroponic Medan, Medan Area District, Medan City for three months, namely from March to June 2023. The survey method is the research strategy used. Utilizing surveys as a data collection tool, the survey method draws samples from existing populations, and its findings can often be applied. The data analysis used is descriptive data analysis by determining the role of marketing channels and marketing margins at Syifa Hydroponic. The results of the study show that the hydroponic vegetable marketing channels at Syifa Hidroponik Medan consist of two marketing channels, namely: Producers - Consumers, Producers - Collectors - Consumers. Marketing channel I is a direct marketing channel, namely hydroponic vegetable producers directly sell pak choi and lettuce to consumers so that marketing channel I does not have a marketing margin. The marketing margin on channel II, namely for pak choi mustard greens is IDR 5,000 and the marketing margin for lettuce vegetables is IDR 5,000. Keywords: marketing, vegetables, hydroponics